2016
DOI: 10.1016/j.rmed.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Lung clearance index for monitoring early lung disease in alpha-1-antitrypsin deficiency

Abstract: Patients with alpha-1-antitrypsin deficiency (AATD) and a PI-ZZ genotype are at high risk to develop severe emphysema during adulthood. However, little is known about early stages of emphysema and disease manifestation in other PI-types. Spirometry is commonly used for monitoring although early manifestation of emphysema is suspected within the peripheral airways that are not accessible by forced expiratory manoeuvres. We hypothesized that the Lung Clearance Index (LCI) derived from multiple breath nitrogen-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
3
9
0
3
Order By: Relevance
“…Our LCI data are well within the range of previous studies [33][34][35]. For example, a recent study using NDD reported a mean LCI of 6.3 in 33 controls (8 to 60 years) whereas it was 6.6 in 101 controls (5 to 65 years) in our study [35].…”
Section: Methodological Considerationssupporting
confidence: 90%
See 1 more Smart Citation
“…Our LCI data are well within the range of previous studies [33][34][35]. For example, a recent study using NDD reported a mean LCI of 6.3 in 33 controls (8 to 60 years) whereas it was 6.6 in 101 controls (5 to 65 years) in our study [35].…”
Section: Methodological Considerationssupporting
confidence: 90%
“…For example, a recent study using NDD reported a mean LCI of 6.3 in 33 controls (8 to 60 years) whereas it was 6.6 in 101 controls (5 to 65 years) in our study [35]. These data are also reassuring that relevant lung disease was clearly absent in our control population though we did not assess spirometry in the latter.…”
Section: Methodological Considerationssupporting
confidence: 65%
“…Spirometry was performed with the Power-Cube Body+ instrument (Ganshorn Deutschland GmbH, Neuenkirchen, Germany). MBW tests were performed by ultrasonic technology using the EasyOne Pro LAB™ (ndd medical technologies AG, Zurich, Switzerland) following the protocol described by Fuchs et al[ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown to detect early lung disease in children and adults and is more sensitive than measures of spirometry (FEV1) in both CF and bronchiectasis (2,5,11). Indices from the MBW test have also been shown to be sensitive to lung disease in asthma (13), COPD (14) and alpha-1-antitrypsin deficiency (20).…”
Section: Mbw Testingmentioning
confidence: 99%